Mathematical Problem-Solving Process Reviewed from Emotional Intelligence through Metacognition: A Literature Review - Kusuma, Reyvall Angling; Rahmawati, Fadila; Murtianto, Yanuar Hery; Baldemor, Milagros (FKIP Universitas Lampung, 2024)
Mathematical Problem Solving Reviewed from Emotional Intelligence through Metacognition: A Literature Review. Metacognition is an essential part of the math problem-solving process, with emotional intelligence helping to maintain student consistency and focus. Objectives: This study aims to provide an overview of research related to the role of metacognition in mathematical problem solving, particularly from the perspective of emotional intelligence, in the period 2013 to 2024. It focuses on how emotional intelligence affects monitoring, evaluating, and controlling cognitive states and regulating students' interpersonal interactions in problem-solving. Method: This study used the PRISMA Method (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) to select relevant literature. Data analysis was conducted with the help of VOSViewers and Bibliometrix R-Package software, which enabled the mapping of relationships between variables and identifying major trends in research. This study focused on articles that explored metacognition in mathematical problem-solving and the impact of emotional intelligence on this process. Findings: The results of this literature review show a 1.21% decrease in metacognition research trends from 2013 to 2024. Metacognition is connected to student variables, cognitive systems, problem-solving strategies, working memory, self-efficacy, active learning, and reflection. The integration of metacognition and emotional intelligence emphasizes their role in mathematics education. Conclusion: This study provides insights for further research on mathematics problem-solving regarding emotional intelligence through metacognition. In addition, variables such as active learning, problem-solving skills, math anxiety, student characteristics, and math awareness can be used as research references relevant to the current generation. Keywords: metacognition, mathematics, problem-solving, emotional quotient. DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp399-418